REALISASI KATEGORIAL DAN SEMANTIS FUNGSI KETERANGAN DALAM BAHASA INDONESIA - Tri Mastoyo Jati Kesuma (Humaniora, 2005)
The paper describes the realizations of adjuncts in Indonesian sentences. Adjunct is an optional syntactic function or constituent in sentences. This constituent can be described from two aspects, i.e. categorial and semantic realizations. The former realization covers noun phrases (e.g. kemarin ‘yesterday’ in Ia mengundurkan diri dari pekerjaannya kemarin ‘He retired from his work yesterday’), prepositional phrases (e.g. pada hari Minggu ‘on Sunday’ in Ibu saya pergi ke Jakarta pada hari Minggu ‘My mother went to Jakarta on Sunday’) and additional clauses (e.g. kalau tidak keliru ‘If I’m not mistaken’ in Kalau saya tidak keliru, Tuan-tuan adalah prajurit Kerajaan Majapahit ‘If I’m not mistaken, you are Majapahit Kingdom soldiers’). The later realization covers temporal, locative, instrumental, manner, benefactive, receptive, agentive, companional, purposive, causative, fundamental, positional and comparative.